2014
DOI: 10.1002/ajim.22329
|View full text |Cite
|
Sign up to set email alerts
|

Using injury severity to improve occupational injury trend estimates

Abstract: Severity restriction may improve occupational injury trend estimates by reducing temporal biases such as increasingly restrictive hospital admission practices, constricting workers' compensation coverage, and decreasing identification/reporting of minor work-related injuries. Injury severity measures should be developed for occupational injury surveillance systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…This study confirms and extends findings from a previous paper that reported similar analyses in fewer states, using an AIS-based threshold rather than this newly developed list 21. Trend estimates were generally biased downwards in the absence of severity restriction, more so for occupational than non-occupational injuries (table 2).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This study confirms and extends findings from a previous paper that reported similar analyses in fewer states, using an AIS-based threshold rather than this newly developed list 21. Trend estimates were generally biased downwards in the absence of severity restriction, more so for occupational than non-occupational injuries (table 2).…”
Section: Discussionsupporting
confidence: 88%
“…There may be a contributory survival shift effect (ie, targeted fatality prevention efforts preventing death but not severe injury or severe injury less often proving fatal due to trauma system improvements). These potential collective or alternative mechanisms have been discussed at more length in previous related publications 21 37 38…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This type of severity score provides a reliable estimate of initial injury severity, independent of patient‐specific factors that may influence hospitalization. In particular, AIS provides more face validity and empirical support as a measure of initial injury severity than do hospital admission or length of stay, both of which can be related to co‐existing conditions, health status, and trends in insurance coverage and standards of care [National Center for Health Statistics (NCHS) Expert Group on Injury Severity Measurement, ; Stephenson et al, ; Cryer and Langley, ; Cryer et al, ; Sears et al, ]. AIS‐based injury severity scores have been validated for prediction of mortality [Baker et al, ; Osler et al, ; Meredith et al, ; Kilgo et al, ; Harwood et al, ], and recent studies have established their association with occupational injury outcomes such as work disability and medical costs [Ruestow and Friedman, ; Sears et al, ].…”
Section: Methodsmentioning
confidence: 99%